Selective removal of lead ions from aqueous solutions using 1, 8-dihydroxyanthraquinone (DHAQ) functionalized graphene oxide; isotherm, kinetic and thermodynamic studies. Issue 11 (2nd February 2018) - Khazaei, Mohammad; Nasseri, Simin; Ganjali, Mohammad Reza; Khoobi, Mehdi; Nabizadeh, Ramin; Gholibegloo, Elham; Nazmara, Shahrokh
Abstract : The Fe3 O4 @DHAQ_GO nanocomposite can serve as an efficient adsorbent for the selective removal of lead from polluted water. Abstract : An anthraquinone – graphene structure was fabricated and applied for the removal of lead(ii ) from aqueous solution. The equilibrium occurred in about 10 min revealing the high adsorption rate at the beginning of the process. The maximum Pb(ii ) adsorption capacity of the Fe3 O4 @DHAQ_GO nanocomposite was about 283.5 mg g −1 that was observed at 323 K and pH 5.5. The Pb(ii ) adsorption ability increased with the increasing pH. The isotherm and kinetic studies indicated that the Sips isotherm model and the linear form of the pseudo-second kinetic model had a better fit with the experimental results. The positive value of Δ H 0 indicated endothermic interactions between Pb(ii ) and Fe3 O4 @DHAQ_GO. The negative Δ G 0 indicated that the reactions are spontaneous with a high affinity for Pb(ii ). The positive Δ S 0 values indicated increasing randomness at the solid–solute interface during the adsorption process. The selective removal of Pb(ii ) by the nanocomposite confirms the presence of higher-affinity binding sites for Pb(ii ) than Cd(ii ), Co(ii ), Zn(ii ), and Ni(ii ) ions. Furthermore, the Fe3 O4 @DHAQ_GO nanocomposite revealed an excellent preferential adsorbent for Pb(ii ) spiked in drinking water samples containing natural ion matrices. EDTA-2NA 0.01 N was found to be a better elution agent than HCl 0.1 M for the nanocomposite regeneration. After five adsorption/desorption cycles using EDTA-2NA 0.01 N, more than 84% of the adsorbed Pb(ii ) was still desorbed in 30 min. Capturing sub-ppm initial concentrations of Pb(ii ) and the capability to selectively remove lead from drinking water samples make the Fe3 O4 @DHAQ_GO nanocomposite practically convenient for water treatment purposes. High adsorption capacity and facile chemical synthesis route are the other advancements.